Urban Furniture in Historical Process - Uslu, Esra; Bölükbaşı, Ayşen Esra (Journal of History Culture and Art Research, 2019)
The city is an artificial environment that forms the settlements of societies formed by different social classes in which people live their lives in accordance with certain rules. These areas have different socio-economic structures that are socially different from each other and therefore have different urban fictions that have been followed throughout the ages. The city is in constant renewal and change. In time, human beings turned to instinct to regulate the physical environment in which they live. The changing environmental forms such as the development of transportation networks and the spread of communication systems have created a more concrete architectural understanding and related environmental regulation. Urban equipment elements have continued to develop as the main elements of these regulations. Urban furniture has contributed to the formation of elements such as communication, aesthetics and functionality in the city, in addition to being the elements that facilitate the personal and social urban life of the individuals forming the society. In a more specific definition, urban furniture are all elements used in landscaping arrangements that respond to basic functions such as sitting, sheltering, transportation, lighting, consultation, communication, games and sports in areas such as streets, roads and squares. The most important features of these elements, which are the building blocks of multi-purpose planning, are the management and direction of pedestrians. Urban furniture emphasizes the rules of living together in order to sustain collective life. Within the scope of this study, historical developments of urban furniture such as sheltered waiting area (stop), lighting element, kiosk, signboard, seating element and garbage can which are the building blocks of cities and contributing to the society to live together in a regular and regulated way are examined.